Hyperthyroidism is not a risk factor for subclinical bacteriuria in cats: A prospective cohort study. (11th April 2020) - Peterson, Mark E.; Li, Alice; Soboroff, Peter; Bilbrough, Graham E.; Rishniw, Mark
Abstract: Background: Subclinical bacteriuria is defined as a positive bacterial urine culture in the absence of clinical evidence of urinary tract infection (UTI). Studies have reported that hyperthyroid cats have UTIs (mostly subclinical) with prevalence rates of 12%‐22%. Consequently, clinicians consider hyperthyroidism a risk factor for development of subclinical bacteriuria, and many recommend urine culture when evaluating hyperthyroid cats. Objectives: To compare the prevalence of subclinical bacteriuria (based on positive urine culture) in untreated hyperthyroid cats to that in euthyroid cats of similar age and sex. Animals: Three hundred and ninety‐three hyperthyroid cats presented for radioiodine treatment and 131 euthyroid cats (≥7 years of age) presented for routine examination. Cats with signs of lower urinary tract disease were excluded. Methods: Prospective cohort study. Both hyperthyroid and euthyroid cats had urine collected by cystocentesis for complete urinalysis and culture. Data pertaining to age, sex, body condition, and serum thyroxine and creatinine concentrations also were acquired. Logistic regression was performed to evaluate for potential risk factors for subclinical bacteriuria. Results: Hyperthyroid cats showed a low prevalence of subclinical bacteriuria (4.3%), which did not differ from that found in euthyroid cats (4.6%). Of the signalment factors evaluated, only female sex was a significant risk factor (odds ratio [OR], 6.9; P = .002). Furthermore, positive urine cultures were more likely in specimens with dilute urine concentration (<1.035), pyuria, or microscopic bacteriuria. Conclusions and Clinical Importance: Hyperthyroid cats are not at risk for subclinical bacteriuria. In the absence of lower urinary tract signs, no clinical benefit exists in routinely performing urine cultures when evaluating hyperthyroid cats.